Adaptasi Skala Quiet Quiting (QQS) pada Karyawan di Indonesia - Juliana Sugandi; Ibnu Zafad Mahbubulhaq; Niken Astrya Murni; Rinaldi Rinaldi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Quiet quitting refers to a phenomenon in which employees do not formally resign from their jobs but intentionally limit their work efforts to the minimum required. This study aims to adapt the Quiet Quitting Scale developed by Galanis et al. (2023) into the Indonesian context. A quantitative approach was employed involving 100 respondents drawn from both private and government sectors. The adaptation process included forward translation by three linguists, synthesis of the translated versions, and cultural adjustment to ensure contextual relevance. Data were analyzed using Confirmatory Factor Analysis (CFA) based on a three-factor model consisting of detachment, lack of initiative, and lack of motivation. The results indicate that the Indonesian version of the Quiet Quitting Scale demonstrates acceptable construct validity across the proposed factors. However, several items still require refinement, suggesting that further development and validation with larger and more diverse samples are necessary to strengthen the scale’s psychometric properties.